(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the science of interpretation, which is widely used in explaining the content of the Qur’an in Islam, its difference from tafsir, and the unique aspects of Ibn Arabi in the method of interpretation are philosophically analyzed.